ANALISIS PERTUMBUHAN SORGUM (Sorghum bicolor (L.) Moench) VARIETAS NUMBU DAN KAWALI PADA BERBAGAI PERLAKUAN BIOMATRICONDITIONING BENIH - Sutariati, Gusti Ayu Kade; Khaeruni, Andi; Guyasa, I Made (Jurnal Agroteknos, 2011)
ABSTRACT The research was aimed to analysis the integration of seed invigoration with rhizobacteria to improve the growth of Numbu and Kawali varieties of sorghum (Sorghumbicolor L.). The experiment design was a randomized block design arranged in Split-plot pattern. The main factor was sorghum varieties which consisted of 2 varieties ie. Numbu and Kawali. The sub plot was seed biomatriconditioning integrated with rhizobacteria treatments which consisted of 5 treatments, namely: control, seed biomatriconditioning with Bacillus sp. CKD061 + rice hulls charcoal, seed biomatriconditioning with Bacillus sp. CKD061 + red brick powder, seed biomatriconditioning with Pseudomonas fluorescens PG01 + rice hulls charcoal, and seed biomatriconditioning with P. fluorescens PG01 + red brick powder. Every treatment was replicated 3 times, therefore, overall there were 30 experimental units. Data obtained were analized using analysis of variance and followed by Duncan’s Multiple Range Test. The result of growth analysis showed that the interaction of both factors significantly influenced the leaf area index, plant growth rate, and net assimilation rate. In both varieties, seed biomatriconditioning with Bacillus sp. CKD061 or P. fluorescens PG01 using red brick powder or rice hulls charcoal were effective in increasing leaf area index, plant growth rate, and net assimilation rate of sorghum compared with untreated treatment. Keywords: biomatriconditioning, rhizobacteria, sorghum